Repression and terrorism: a cross-national empirical analysis of types of repression and domestic terrorism - Piazza, James A. (Terrorism and political violence, 2017)
While some scholars have theorized that repression reduces terrorism because it raises the costs of participating in terrorist activity by dissidents, others argue that repression stimulates terrorism by either closing off nonviolent avenues for expressing dissent or by provoking or sharpening grievances within a population. This study investigates these contradictory sets of expectations by considering whether or not different specific types of repression yield different effects on patterns of terrorism in 149 countries for the period 1981 to 2006. By assessing the impact of nine specific types of repression on domestic terrorism, the study produces some interesting findings: while, as expected, forms of repression that close off nonviolent avenues of dissent and boost group grievances increase the amount of domestic terrorism a country faces, types of repression that raise the costs of terrorist activity have no discernible suppressing effect on terrorism.